Miejsca Cogito. Narracje megalomanii i melancholia początków - Nowak, Maciej (Er(r)go. Teoria - Literatura - Kultura, 2008)
Maciej Nowak The Whereabouts of Cogito. Narratives of Megalomania and the Melancholy of the Beginning The title of the article is a cluster of various plays on words which build up an allusion to classic texts and “situations” that should sound familiar to most humanists. The title suggests that cogito is not an epistemological post of certitude but it has its “whereabouts” – so its axiological and discursive character cannot be pinned down and endowed with an ultimate sense of some kind. Consequently, the dynamic and perhaps furtive nature of cogito is tainted by the author’s (Descartes’s) megalomania or, to put it bluntly, the philosopher’s arrogant claim of his being able to access objective truth and authoritatively define the firm fundament of all knowledge. The article shows that this aspiration cannot be fulfilled (hence the titular melancholy, a word alluding to both Derrida and Levi-Strauss) and that it has been the nature of grand philosophical projects to get embroiled in complex semantic, conceptual, stylistic, textual trouble spots.